Channel selection strategies for co-existence between wimax and wifi - Jong, Siat Ling (2009)
Cognitive radio (CR) is a paradigm for wireless communication in which a wireless node changes its transmission or reception parameters to communicate efficiently avoiding interference with licensed or unlicensed users. The utilization of spectrum is one of the critical issues in development of cognitive radio. Therefore, channel selection algorithm is developed to select the best operating band which can maximize the total system performances. This project study the spectrum co-existence between IEEE 802.16a and 802.11b network in the same un-licensed band using cognitive radio technique. A channel selection algorithm is proposed to improve the secondary user's throughput and avoid interference with primary user. NS2 simulation model is presented to evaluate the channel selection in scenarios with co-existing IEEE 802.16a and 802.11b network